2015
DOI: 10.1175/jcli-d-14-00311.1
|View full text |Cite
|
Sign up to set email alerts
|

Resolution Dependence of Future Tropical Cyclone Projections of CAM5.1 in the U.S. CLIVAR Hurricane Working Group Idealized Configurations

Abstract: The four idealized configurations of the U.S. CLIVAR Hurricane Working Group are integrated using the global Community Atmospheric Model version 5.1 at two different horizontal resolutions, approximately 100 and 25 km. The publicly released 0.9° × 1.3° configuration is a poor predictor of the sign of the 0.23° × 0.31° model configuration’s change in the total number of tropical storms in a warmer climate. However, it does predict the sign of the higher-resolution configuration’s change in the number of intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
116
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 44 publications
13
116
0
Order By: Relevance
“…1 shows the simulated global TC numbers range from small values to numbers similar to those observed (Zhao et al 2013a,b;Shaevitz et al 2014). Better results can also be obtained from higher-resolution versions of the HWG models (finer than 50-km horizontal resolution), including an ability to generate storms of intense tropical cyclone strength, as shown by Wehner et al (2014) for a higher-resolution version of the NCAR CAM5 than that shown in Fig. 1.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…1 shows the simulated global TC numbers range from small values to numbers similar to those observed (Zhao et al 2013a,b;Shaevitz et al 2014). Better results can also be obtained from higher-resolution versions of the HWG models (finer than 50-km horizontal resolution), including an ability to generate storms of intense tropical cyclone strength, as shown by Wehner et al (2014) for a higher-resolution version of the NCAR CAM5 than that shown in Fig. 1.…”
mentioning
confidence: 51%
“…While it is clear that simply increasing the resolution does not necessarily improve intensity distribution (Shaevitz et al 2014), results from the HWG simulations indicate that a very significant improvement in a GCM's ability to simulate both TC formation and intensity occurs at resolutions finer than 50 km, with good results shown at 25 km (Strachan et al 2013;Roberts et al 2015;Lim et al 2015;Wehner et al 2015;Mei et al 2014). In addition, if such high resolution is employed, it is possible to simulate reasonably well the observed intensity distribution of tropical cyclones (Bender et al 2010;Lavender and Walsh 2011; Murakami et al 2012b;Chen et al 2013;Zarzycki and Jablonowski 2014).…”
Section: Simulation Of the Intensity Distribut Ion Of Tr O Pical Cyclmentioning
confidence: 97%
“…For example, results from LaRow et al [2008] demonstrate that a GCM with a T126 horizontal resolution (0.948) reasonably simulates the effect of the El Niño/Southern Oscillation on North Atlantic TC frequency beginning in 1995. Furthermore, recent higher-resolution modeling studies by Wehner et al [2015] and Zarzycki and Jablonowski [2014] successfully generate TCs with wind speed distributions that better match observations. These results suggest that as resolution continues to improve, climate models may be able to better predict not only future changes in TC frequency, but also intensity.…”
Section: Introductionmentioning
confidence: 91%
“…Much of this previous research examines GCM simulations spanning several resolutions to compare TC frequency and intensity statistics among model runs. For example, Wehner et al [2015] present the effects of model resolution on the ability of the Community Atmosphere Model (CAM5) to generate intense TCs and simulate inter/intraannual variability. As expected, the 0.258 version of the CAM5 generates much stronger TCs (including some Category 5 hurricanes on the Saffir-Simpson scale) when compared to the 18 and 28 model simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation